THE STUDY OF OSTEOPROTECTIVE PROPERTIES OF NANOPARTICULATED FORMS OF RESVERATROL AND LOSARTAN - Ivan Koklin; Oleg Gudyrev; Alexander Faitelson (Research Results in Pharmacology, 2015)
The study demonstrated that endothelial dysfunction of bone microvasculature and deterioration of regional blood flow in bone developed eight weeks after ovariectomy in female white Wistar rats thus raising the risk of generalized osteoporosis. Nanoparticulated forms of losartan and resveratrol possessing endothelioprotective action effectively prevented reduction of regional microcirculation in bone tissue through keeping it at the same level as intact rats had. It allowed maintaining an adequate level of bone remodeling processes which was manifested in slowing of thinning of bone trabeculas and in prevention of possible microfractures in them.